Thailand’s BRICS move revisited - Thapiporn Suporn; Poowin Bunyavejchewin (Cogent Social Sciences)
This study explores Thailand’s pursuit of BRICS membership through the lenses of Teo’s middle power theory and Kuik’s theory of regime legitimation, based on archival and secondary materials. Methodologically, a case study research design with a process tracing technique is employed. The key findings indicate that internal and external conditions drove Thailand’s BRICS move. Externally, the stratified international structure has motivated the country, self-proclaimed as a middle power, to preserve, if not elevate, its international standing by differentiating itself from smaller nations through active engagement in multilateralism, including the pursuit of BRICS membership. Internally, maintaining regime legitimacy has shaped Thai foreign policy actions towards BRICS, thereby supporting the domestic agendas of the political party in power. The delay in becoming a full member of BRICS from the time publicly anticipated may imply that policymakers in Bangkok need to do more to distinguish the country and demonstrate its value-added to BRICS compared to other middle powers seeking the same status.